Interprétation générique des indéfinis français et slovenes - Struna, Tatjana (Vestnik za tuje jezike, 2012)
This study focuses on the contrastive analysis of French and Slovene indefinite determiners, with a special emphasis on the standard generic and partial generic interpretation of selected indefinite determiners. In the study, it is examined how the semantic, syntactic and pragmatic features of tout(e/s), chaque, quelque, plusieurs, certains and their Slovene equivalents (vsi, vsak, nekaj, več, nekateri) influence the two interpretations. Within the scope of the two interpretations, it is studied how the indefinite determiners in the subject or object can influence the final result, what are the restrictions that prevent the repetition of the same quantifier in the same sentence, and why it is sometimes impossible to keep the same interpretation with the same meaning in both languages. The aim of this work is to show the similarities and differences of generic interpretations between both languages. Although the French has an article that can express the genericity more easily than Slovene, there are no special markers neither in French nor Slovene to express the genericity. It is shown that genericity does not depend on a form but on the interpretation (context and situation) of the sentence.
Keywords: francoščina; French; Slovene; slovenščina; kontrastivna analiza; določevalniki; nedoločni določevalniki; pridevniški zaimki; samostalniški zaimki; semantics; semantika